Letter: liver disease and COVID‐19—not the perfect storm. Issue 3 (13th July 2020) - Nathwani, Rooshi; Mukherjee, Sujit; Forlano, Roberta; Mullish, Benjamin H.; Vergis, Nikhil; Selvapatt, Nowlan; Manousou, Pinelopi; Nayagam, Shevanthi; Lemoine, Maud; Dhar, Ameet
Abstract : LINKED CONTENT This article is linked to Garrido et al papers. To view these articles, visit https://doi.org/10.1111/apt.15813 and https://doi.org/10.1111/apt.15886 .